2001
DOI: 10.1046/j.1432-1327.2001.02008.x
|View full text |Cite
|
Sign up to set email alerts
|

A change in ionization of the NADP(H)‐binding component (dIII) of proton‐translocating transhydrogenase regulates both hydride transfer and nucleotide release

Abstract: Transhydrogenase couples the transfer of hydride-ion equivalents between NAD(H) and NADP(H) to proton translocation across a membrane. The enzyme has three components: dI binds NAD(H), dIII binds NADP(H) and dII spans the membrane. Coupling between transhydrogenation and proton translocation involves changes in the binding of NADP(H). Mixtures of isolated dI and dIII from Rhodospirillum rubrum transhydrogenase catalyse a rapid, single-turnover burst of hydride transfer between bound nucleotides; subsequent tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…In addition to movement of the entire domain, loop D within domain III also undergoes conformational change. 23,50,51 This is observed in crystals of R. rubrum domain III with two molecules in the asymmetric unit. 27 Loop D displays an open conformation, as seen in the dI 2 dIII complexes, and a closed conformation, in which the entire loop (b subunit residues 396-413) closes over NADPH.…”
Section: Domain III Within Thmentioning
confidence: 75%
“…In addition to movement of the entire domain, loop D within domain III also undergoes conformational change. 23,50,51 This is observed in crystals of R. rubrum domain III with two molecules in the asymmetric unit. 27 Loop D displays an open conformation, as seen in the dI 2 dIII complexes, and a closed conformation, in which the entire loop (b subunit residues 396-413) closes over NADPH.…”
Section: Domain III Within Thmentioning
confidence: 75%
“…The rate constants for release of NADP ϩ and of NADPH from isolated dIII greatly increase at low pH (33). The data suggested that nucleotide release from dIII is preceded by protonation, and the possibility was raised that this might correspond to a step in proton translocation in the intact enzyme.…”
Section: Resultsmentioning
confidence: 98%
“…The change in NADPH fluorescence as it rebound to dIII was negligible. NADP ϩ release from the E155W mutant of dIII following addition of excess NADPH was measured from the change in Trp fluorescence (15,33). The dIII protein (with or without dI) was pre-incubated in 20 mM Mops, pH 7.2, containing 20 M NADP ϩ , at 20°C for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of excess NADPH, bound NADP ϩ is displaced from the dIII component on a time scale of a few minutes (27). Table I shows that the effect of exchanging NADP ϩ for NADPH on the phosphorescence lifetime of Trp-72 in dI 2 ⅐dIII 1 complexes is very small.…”
Section: Effects Of Nadh Binding On the Phosphorescence Of Di-di Bindmentioning
confidence: 99%